Improved receiver system for laser range finder - Saniei, Soodeh Zahab (2010)
This thesis discusses on the design and development of Laser Range Finder receiver for long range measurement application with concentration on Time of Flight (TOF) concept for range estimation. In TOF method, a laser pulse is emitted from transmitter through the target and the reflected pulse from the target would be detected in pulse detector circuit of the receiver adjacent to the transmitter. By measuring the time of flight of this pulse, the corresponding distance can be obtained. The designed receiver of this research has two major parts. First is pulse detector circuit that is designed to operate with 50 ns pulse as the input, representing the output of photo diode at receiver that will be provided by pulse generator in this research. For variable sensitivity, which is necessary in long distance range finders, the pulse detector circuit was designed based on variable offset strategy together with variable detecting threshold instead of variable gain, as variable gain is more difficult in control with complex circuitry. For short distance, in which the reflected signal is less attenuated and background noise is stronger, the amount of added DC offset is higher (so the difference between main signal and threshold increases), and for long distances it reduces gradually to zero. The main signal experiences variable offset before passed to the comparator to be detected. This is a very important part resulting in variable sensitivity in receiver. This signal will be compared to a variable detecting threshold in comparator. The variable threshold voltage in the comparator consists of three parts. The first part produced by peak detector, is proportional to the amount of noise in the signal to eliminate its effect in detection, which contributes towards more accurate measurement. The second part is the output of low pass filter that acts as an integrator, which is the baseline of the signal. Finally, the third part is a DC voltage for eliminating the undesired voltages, which are the effects of inverter output (when it is saturated) and variable offset, in the output of integrator. Applying this variable threshold for reflected pulse detection results in reducing false detection and noise and eliminate dc effects. Another part of receiver is counter that is designed and developed using Field-Programmable-Gated-Array (FPGA). FPGA does not only perform high accuracy timing but converts the time to corresponding distance as well. The frequency of operation is adjusted on 200 MHz. It means that the time intervals as short as 5 ns can be measured resulting in a distance accuracy of 0.75 m, which is a good accuracy for long distance measurement. The experimental results from pulse detector circuit show that applying variable offset leads to variable sensitivity and variable detecting threshold can reduce the effects of noise and DC offset in detection process. In addition, by implementing this method, the circuit will be much more simplified and easy to control in comparison with common methods.